Radiation hazards and natural radioactivity levels in surface soil samples from dwelling areas of North Cyprus - Abbasi, Akbar; Kurnaz, Asley; Turhan, Şeref; Mirekhtiary, Fatemeh (Springer Science and Business Media LLC, 2020)
Due to increasing concern about environmental radiological protection, radioactivity concentrations of 226Ra, 232Th, 40K and 137Cs in surface soil samples collected from the North area of Cyprus have been determined using a high-resolution HPGe gamma-spectroscopy system. The range of activity concentrations of 226Ra, 232Th, 40K and 137Cs in the soil samples varies from 49.7 ± 3 to 147.6 ± 17.2, 18.1 ± 1.5 to 93.9 ± 10.7, 103.5 ± 27 to 1468.6 ± 176.1 and 4.3 ± 0.1 to 15.9 ± 1.3 Bq kg−1, respectively. The obtained results and calculated values of radiation dose in the study area indicate that the relatively high background radioactivity levels.
Keywords: 13. Climate action